Peran Citra Bank Muamalat Kantor Cabang Madiun Dalam Membentuk Loyalitas Nasabah - Safitri, Alfika Waya; Lisdiantini, Netty; Hastuti, Farida Tri (Politeknik Negeri Madiun, 2023)
Every bank tries to offer the best choices and facilities attracting customers due to the emergence of new competitors operating in the same field; with this, the bank is certainly trying to maintain its image well. The image of a bank is important for a company because it maintains its customers so that they remain loyal, and even non-customers can be attracted to the bank and not switch to existing competitors. This research aims to determine the role of the image of the Bank Muamalat Madiun Branch Office in forming customer loyalty. The research method used is a quantitative method using a questionnaire as a data collection instrument. The sample in this study used 30 respondents with purposive sampling data collection techniques. The primary data used is a questionnaire, and secondary data is obtained through documents such as books and articles. The research results show that there is a role or influence on the image of Bank Muamalat Madiun Branch Office in forming customer loyalty, as proven by the results of hypothesis test calculations (t-test). It can be seen that the significance value obtained is 0.000